Distributed acoustic sensing/surface orbital vibrator: Rotary seismic sources with fiber-optic sensing facilitates autonomous permanent reservoir monitoring - Correa, Julia; Isaenkov, Roman; Yavuz, Sinem; Yurikov, Alexey; Tertyshnikov, Konstantin; Wood, Todd; Freifeld, Barry M; Pevzner, Roman (SOC EXPLORATION GEOPHYSICISTS, 2021)
With new developments of fiber-optic sensing and rotary sources, continuous active seismic monitoring for onshore applications has now the opportunity to be fully realized and applied to enhance subsurface resource extraction and use. To date, conventional seismic monitoring deployments have primarily consisted of receiver arrays, either fixed or not, with periodic data acquisition campaigns using temporarily deployed sources, resulting in time-lapse data with poor temporal resolution. Only a few niche efforts have demonstrated continuous acquisition using fixed source-receiver networks. We have evaluated the initial results of a network of fixed rotary seismic sources, referred to as surface orbital vibrators (SOVs), coupled with a permanent distributed acoustic sensing (DAS) network at the CO2CRC Otway Field Site. Although rotary seismic sources are not new, our development of the SOV focused on simplifying the cost and complexity of the source hardware while delivering broad frequency spectrum of the source signal. The upgraded hardware is aligned with a robust methodology for autonomous operation and data processing. At the Otway Site, we deployed SOVs at nine locations, monitoring seismic response in seven DAS instrumented wells. Baseline operation of the DAS/SOV sensor array and source system demonstrates its capability with near offsets attaining a signal-to-noise ratio approaching 100 dB with a normalized root mean square of 10%. Furthermore, analyses of traveltime repeatability indicate that the DAS/SOV system can deliver time resolution of ±500 μs.